Spirit and Healing in Africa A Reformed pneumatological perspective - van den Bosch-Heij, Deborah (UJ Press, 2013)
There is a great need for healing in Africa. This need is in itself no different elsewhere in the world, but it is greatly determined by the involvement of religious communities and traditions. Faith communities and religious institutions play a major role in assisting African believers to find health, healing and completeness in everyday life.